2019
DOI: 10.1186/s13287-019-1222-0
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of F-box proteins in the regulation of epithelial-mesenchymal transition and stem cells in human cancers

Abstract: Emerging evidence shows that epithelial-mesenchymal transition (EMT) plays a crucial role in tumor invasion, metastasis, cancer stem cells, and drug resistance. Data obtained thus far have revealed that F-box proteins are critically involved in the regulation of the EMT process and stem cell differentiation in human cancers. In this review, we will briefly describe the role of EMT and stem cells in cell metastasis and drug resistance. We will also highlight how numerous F-box proteins govern the EMT process an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 149 publications
(172 reference statements)
1
20
0
Order By: Relevance
“…We found that FBXL8 blocks apoptosis of BRCA cells and modulates cytokine profiles to promote a pro-inflammatory condition. Furthermore, we showed that knockdown of FBXL8 induced intrinsic apoptosis of the BRCA cells, suggesting that FBXL8 promotes BRCA advancement, as supported by the involvement of other F-box proteins in regulating the EMT process in cancers [14]. Consistently, we demonstrated that the loss of FBXL8 decreased cell migration and invasion, affirming that FBXL8 is a key promoter of BRCA progression and metastasis.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that FBXL8 blocks apoptosis of BRCA cells and modulates cytokine profiles to promote a pro-inflammatory condition. Furthermore, we showed that knockdown of FBXL8 induced intrinsic apoptosis of the BRCA cells, suggesting that FBXL8 promotes BRCA advancement, as supported by the involvement of other F-box proteins in regulating the EMT process in cancers [14]. Consistently, we demonstrated that the loss of FBXL8 decreased cell migration and invasion, affirming that FBXL8 is a key promoter of BRCA progression and metastasis.…”
Section: Discussionsupporting
confidence: 74%
“…To test this hypothesis, we first identified the specific SCF E3 ligases and their potential pathobiological partners, and then explore their mechanisms in driving BRCA progression, with a view to understanding how the SCF E3 ubiquitin ligases might act as significant risk factors in cancer advancement [ 13 ]. Since the F-box is responsible for the functional specificity of SCF E3 tetrameric complex [ 14 ], we focused our attention on the expression profiles of F-box factors. Notably, there are 71 genes in the human “F-box gene family”, including: (1) 21 F-boxes grouped as leucine-rich repeat protein, (2) 11 F-boxes with WD repeat domain and (3) 39 F-boxes grouped as “others” [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its special relevance is also highlighted by the fact that it appears to reveal co-occurrence with two mutations, specifically RB1 and PIK3CA, which were also detected in the presented cases. Other genes related to neuroendocrine differentiation, like ASCL1, may also play a role in the development of the neuroendocrine component, especially since ASCL1 is involved in the Notch-Hes1 axis, which is analogous to the Wnt-beta catenin signalling pathway, altered by the FBXW7 mutation [51][52][53]. Our findings may expedite the understanding of combined tumour development in the colon and in addition help establish awareness for such rare neoplasms, although continuing research, especially with regard to divergent differentiation of neuroendocrine-and squamous-related genes, is necessary to fully decode the development of this combined neoplasm.…”
Section: Woischke Et Almentioning
confidence: 99%
“…F-box proteins have been validated to play a pivotal role in carcinogenesis and progression 13,15 . They are involved in various physiological and pathological processes which include proliferation, apoptosis, metastasis, cancer stem cell generation, epithelial-mesenchymal transition (EMT), drug resistance in human cancers [16][17][18] . It is important to notice that F-box proteins, including FBXO22, have oncogenic or tumor suppressive role in cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%